THE SIGNIFICANCE OF RESEARCH RESULTS USING PSYCHO-ACOUSTIC METHODS IN CONNECTION WITH ELECTROPHYSIOLOGICAL METHODS IN THE TREATMENT OF PATIENTS WITH INITIAL SENSONEURAL HARDNESS OF VASCULAR ORIGIN - Shidlovsky, A.Yu. (The Ukrainian Scientific Medical Youth Journal, 2017)
The results of examination and treatment of 93 patients with the beginning of sensoneural hearing loss of vascular genesis. The importance of complex examination of these patients with the use of psychoacoustic methods in connection with electrophysiological (rheoencephalo- graphy, electroencephalography, short-latent and long- latent auditory potentials) has been shown to improve the topical diagnosis and the effectiveness of treatment of such patients. The aim of the work is to analyze the results of the study by psychoacoustic methods in connection with electrophysiological (rheoencephalography, electroencephalography, short-latent and long latent auditory potentials) in patients with initial sensoneural hearing loss of vascular genesis and to treat them with the revealed changes, as well as the vascular factor that it accompanies, which will help improve the quality of their topical diagnosis and treatment effectiveness. The use of the results of modern psychoacoustic research methods in connection with electrophysiological: hearing study in the extended frequency range, recording of short and long-latent auditory evoked potentials, rheoencephalography and electroencephalography, in the study of patients with sensoneural hearing loss in the early stages of its development, improves the quality of their diagnosis and opens the possibility of developing more based complex and effective methods of treatment and sensoneural hearing loss. Assessment of the functional state of the auditory analyzer and the brain as a whole in accordance with the data of short-and long-latent auditory evoked potentials, electroencephalography, and cerebral circulation according to rheoencephalography, and if necessary, ultrasonic dopplerography of the vessels of the head and neck are necessary components in the treatment of patients with initial sensoneural deafness of vascular origin. Based on the results obtained, the effectiveness of treatment of patients with initial sensoneural hearing loss of vascular genesis before and after treatment was estimated from data not only of subjective, but also objective methods of investigation. It is also important that the assessments of the effectiveness of treatment of patients with the presence of sensoneural hearing loss of vascular genesis were first given according to data not only of subjective, but also objective audiometry.